The The Effect of Different Depths of Growth Rate of Gracilaria sp. in Silvofishery Ponds at in Tambakbulusan Village, Demak: Effect of Different Depths of Growth Rate of Gracilaria sp. in Silvofishery Ponds at in Tambakbulusan Village, Demak - Nurul Aulia Dinastuti; Sri Rejeki; Pujiono Wahyu Purnomo (Journal of Aquaculture and Fish Health, 2026)
Seaweed cultivation in the silvofishery system is one of the efforts to utilize environmentally friendly pond land while supporting the sustainability of fisheries production and mangrove ecosystems. The Demak region, especially in the Tambakbulusan village pond area, has great potential for the development of seaweed cultivation of the Gracilaria sp. This study aims to analyze the effect of differences in depth on the growth rate of Gracilaria sp. in silvofishery ponds so as to provide recommendations for farmers in dealing with changes in the aquatic environment. The parameters measured include absolute weight, Specific Growth Rate (SGR), and water quality. The results of the measurement of the absolute weight of Gracilaria sp. showed a difference between cultivation depths of 20 cm (190.67 ± 12.90 grams), 40 cm (155.67 ± 31.21 grams), 60 cm (88.67 ± 14.36 grams). The results of the study on SGR measurements (% / day) of Gracilaria sp. showed differences between cultivation depths of 20 cm (2.37 ± 0.10 grams), 40 cm (2.07 ± 0.47 grams) and 60 cm (1.41 ± 0.12 grams). Water quality data showed temperature (29.4–32.9°C), pH (8–8.1) and dissolved oxygen (3.5–7.4 mg/l). Brightness (33–36 cm), salinity (32.9–33.5 ppt) as well as nitrate (0.67–1 mg/l) and phosphate (0.38–1 mg/l) were sufficient for the growth of Gracilaria sp. seaweed.